Polish citizens in Brazil - Kukawska, Agata Edyta (Biuletyn Historii Wychowania, 2023)
This is a presentation of Polish immigrants who came to Brazil in the 19th and 20th centuries, now the second biggest Polish community in the world. In my presentation, I intend to describe the reason of the emergence of the population. Then, I continue to show the history of the community in Brazil, especially in Curitiba, the “Polish’’ capital of Brazil. Next in my presentation is the situation of the population of Polish origin in Brazil. I present different organisations which are a part of this community. What is more, I also describe the Parana region as a with the biggest concentration of residents with Polish roots. I also mention how Polish traditions are cultivated.